2022
DOI: 10.3390/bioengineering9070281
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Smartphone-Based Expert System for COVID-19 Risk Prediction at Early Stage

Abstract: COVID-19 has imposed many challenges and barriers on traditional healthcare systems due to the high risk of being infected by the coronavirus. Modern electronic devices like smartphones with information technology can play an essential role in handling the current pandemic by contributing to different telemedical services. This study has focused on determining the presence of this virus by employing smartphone technology, as it is available to a large number of people. A publicly available COVID-19 dataset con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The IoMT framework addresses the shortage of resources faced by medical teams during the COVID-19 epidemic; not only can the geo-location of COVID-19 patients be tracked by Bluetooth to assess personnel risk [ 26 , 27 , 31 , 40 ], but the technology allows for tracking of patient recovery [ 22 , 33 ]. Chen’s research focuses on visualizing and discussing this important information [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The IoMT framework addresses the shortage of resources faced by medical teams during the COVID-19 epidemic; not only can the geo-location of COVID-19 patients be tracked by Bluetooth to assess personnel risk [ 26 , 27 , 31 , 40 ], but the technology allows for tracking of patient recovery [ 22 , 33 ]. Chen’s research focuses on visualizing and discussing this important information [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a decrease in miR146a-5p may indicate HIV infection [ 93 ] and could serve as both a diagnostic and prognostic factor in COVID-19 [ 36 , 37 ]. Consequently, HRV monitoring is undoubtedly worth including in smartphone-based or other expert systems for disease prediction at early stages, or for outcome prediction, which is not yet performed routinely [ 94 , 95 , 96 ].…”
Section: Discussion: Novel Therapies Targeting Vagus Nerve Stimulatio...mentioning
confidence: 99%
“…The combination of partial least squares-discriminant analysis (PLS-DA) for feature selection and adaptive synthetic sampling (ADASYN) for data balancing demonstrates the best overall performance, offering promising precision medicine prospects for diabetes treatment. Finally, Raihan et al [30] explores the use of smartphone technology to detect the presence of COVID-19, given the challenges and risks posed by the pandemic. To address the class imbalance issue in the COVID-19 dataset, Adaptive Synthetic Sampling (ADASYN) is employed.…”
Section: Adasyn Data Balancingmentioning
confidence: 99%
“…Yet, machine learning algorithms frequently encounter challenges such as outliers and imbalanced datasets, which can reduce accuracy. Research has demonstrated that addressing these issues by applying the Isolation Forest (iForest) method to remove outliers [23][24][25][26][27] and utilizing Adaptive Synthetic Sampling (ADASYN) for balancing imbalanced data [28][29][30][31][32][33][34][35] can lead to improved predictive system performance.…”
Section: Introductionmentioning
confidence: 99%